Identificação e classificação de áreas úmidas costeiras relacionadas à valoração de seus serviços ecossistêmicos na ilha de Santa Catarina (Florianópolis) – Brasil - Teixeira, Marcela Ribeiro e Silva (2020)
The uncontrolled growth of the population occurs mainly in coastal areas, resulting in a new form of appropriation of nature that intensifies and change the characteristics of the landscape. The impact caused becomes dangerous for the conservation of ecosystems, mainly coastal wetlands and their ecosystem services, which even covering 1.5% of the earth’s surface, represent 40% of the essential natural services offered to humanity. The services offered include, among others: periodic water supply; retention of flood pulses and sediments; purifies water; aquifer recharge and groundwater. The conservation of these areas guarantees the survival and well-being of humans and the ecosystem. For this, however, it is necessary to have reliable information to generate public policies that keep them conserved. Thus, the work aims to identify, measure and compare the coastal wetlands of Santa Catarina Island within the boundary of the Jurerê and Ratones hydrographic basins, in the years 1957 and 2016, relating them to their available ecosystem services using the valuation as an indicator. Monetary value of these services. For this purpose, a dichotomous switch was made to identify the coastal wetlands found through QGIS, to later identify ecosystem services with the help of the CICES V5.1 system, and finally to value the services through the transfer of benefits. A loss of 33.86% was observed in coastal wetlands in the 59-year interval and consequently there was a loss of 38,523,225.36 (R $ / ha / year) in ecosystem services. To regularize public policies that value the conservation of the environment, it is necessary to understand how it works, what it can provide for society and how it has been affected by the demographic growth of the region. Therefore, it is extremely important to identify and classify areas of social and biological interest, their available services, and the negative impacts brought to the population, serving as an argumentative basis for their conservation.